Avaliação do neurodesenvolvimento em crianças e sua associação com a pré-eclâmpsia: um estudo transversal - Concha Iparra, Alejandra (2025)
Hypertensive disorders of pregnancy (HDP) are among the leading causes of morbidity, mortality, hospitalization, and maternal-infant resource consumption worldwide. Among these conditions, preeclampsia stands out as one of the most frequent and severe complications, being the leading cause of maternal morbidity and mortality in Brazil, with an incidence of 10%. Studies indicate that preeclampsia is associated with an increased risk of adverse outcomes in infant neurodevelopment. This study assessed the neurodevelopment of children between 11 months and 0 days and 12 months and 30 days, born to mothers with and without preeclampsia. It is a cross-sectional comparative study conducted at the Maternidade-Escola Assis Chateaubriand (MEAC). Data collection included information extracted from medical records regarding sociodemographic characteristics, gynecological-obstetric history, pregnancy aspects, delivery, and newborn conditions, as well as the application of the Ages and Stages Questionnaire - Third Edition (ASQ-3) to assess infant neurodevelopment. Data were analyzed using Microsoft Excel and the Statistical Package for the Social Sciences (SPSS), version 21.0, through cross-tabulation, Pearson's chi-square test, and binary logistic regression. The study was approved by the Research Ethics Committee of the Maternidade-Escola Assis Chateaubriand (MEAC) under the CAAE number 80803124.8.0000.5050, following the guidelines of Resolution 466/2012 and the principles of the Declaration of Helsinki. The results indicated a tendency toward a higher risk of cognitive development impairment in term infants exposed to preeclampsia. The study reinforces the need to strengthen prenatal and postnatal care programs, promoting comprehensive monitoring of child development, especially in infants with perinatal risk factors such as exposure to pre-eclampsia.